ENHANCING DESCRIPTIVE WRITING ACHIEVEMENT BY APPLYING PROCESS APPROACH THROUGH ENVIRONMENTAL OBSERVATION - Febriyanti, Riana; Inderawati, Rita; Fiftinova, Fiftinova (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This study aimed at finding out whether or not: (1) there was a significant difference in descriptive writing achievement after they were taught by using process approach through environmental observation and (2) there was a significant difference in descriptive writing achievement between the students who were taught by using process approach through environmental observation and those who were not. By employing a quasi-experimental design, the sample of this study was 80 students of tenth graders of SMA Negeri 9 Palembang taken by using purposive sampling method. The data were analyzed by using paired sample and independent sample t-test. The result of this study showed that: (1) there was significant improvement in descriptive writing achievement of the experimental group; mean difference of post-test and pre-test was 7.500 and the significance value was 0.000 (p-value0.05), and (2) there was significant difference in descriptive writing achievement between the students who were taught by applying process approach through environmental observation and those who were not. The mean difference of the post-test of the experimental group was higher than the control group (7.5370.128) and the significance value was 0.000 (p-value0.05). Therefore, process approach through environmental observation is effective to enhance students descriptive writing achievement.